K.H. NAWAWI BANTEN (w.1314/1897) Akar Tradisi Keintelektualan NU - Mamat Slamet Burhanuddin (State Islamic University North Sumatra, 2010)
Abstract: K.H. Nawawi Banten (w. 1314/1897): The Root of Intellectual Tradition of NU. The emergence of young ‘liberal’ thinkers from the NU tradition has surprised many, partly because this organization has always been pictured as intellectually conservative and traditional. The present author argues that in fact NU has excellent roots to support modern intellectual undertakings by examining the life, works, and the methodology of K.H. Nawawi Banten, whose thought was considered to be very influential in the formation of NU intellectual tradition.Kata Kunci: NU, Nawawi Banten